The equation parallel to y = -3x + 4 has the same slope which is -3.
Recall that the general equation of a line is represented as :
![y\text{ = mx +c}](https://img.qammunity.org/2023/formulas/mathematics/college/lsv9yhrv64gi9ivaiavq77fqqkajuev2ue.png)
Where m is the slope of the line
Since the line passes through (-3, 4), we can use the slope formula to find the required equation.
The slope formula is:
![\text{slope = }(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2023/formulas/mathematics/college/n33y9wwyhbux9pk4zdwi6s69fk1lz02jyz.png)
Substituting we have:
![\begin{gathered} -3\text{ = }(y-4)/(x-(-3)) \\ y-4\text{ = -3(x + 3)} \\ y\text{ = -3x -9 + 4} \\ y\text{ = -3x -5} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kk6s9bqkj1kzx9ch84cvigamjls11qsn9x.png)
Answer: Option 4